Investigation of the mechanical and in vitro biological properties of ordinary and white Portland cements - Pincha Torkittikul (2018)
Biomaterials containing calcium silicate have been widely used in dental and bone repaired applications. This study investigated mechanical and in vitro biological properties of ordinary and white Portland cement both of which are composed mainly of calcium silicates. The time of setting was determined using a Vicat needle. Compressive strength was measured at the age of 1, 3, and 7 days. The 1 day set Portland cement pastes were soaked in a simulated body fluid to investigate the ability of the material to form a bond with living bone tissue. X-ray diffraction traces of samples following immersion in simulated body fluid demonstrated that both cement pastes form a hydroxyapatite layer within 7 days but white Portland cement shows a noticeably higher amount of apatite crystal than that of ordinary Portland cement. Scanning electron micrographs reveal a clear presence of hydroxyapatite on the surface of white, but not in ordinary Portland cement. In addition, white Portland cement can achieve a compressive strength of 30 MPa within 24 h after curing in distilled water at human temperature.